Bye bye Brasil: ​ ​experiências migratórias de brasileiros graduados que emigraram para a Inglaterra dispostos a realizar trabalhos que nunca consideraram fazer no Brasil - Monique Salomon Giuliani (2019)
Among the main places of destination of Brazilians who decide to migrate to another country, is England that currently houses one of the largest communities of Brazilians living abroad.Many of these Brazilian immigrants, before emigrating, made investments in their human capital, dedicating time and money to a higher education course in order to obtain a better placement in the Brazilian labor market. These Brazilian graduates migrate, in many cases, willing to carry out in the receptor country, in this case England, jobs that they had never considered in Brazil such as cleaner, driver, babysitter, among other jobs belonging to what Piore (1994) names the secondary market. Thus, this research aims to analyze migratory experiences of Brazilian graduates who legally migrated to England willing to perform low-skilled jobs in England. It is intended, through the methodology of collecting life reports, to verify: how the desire to migrate emerged; attraction and repulsion factors that resulted in the decision to migrate; obstacles encountered; what the expectations before migrating were; what the last position held before migration and professional career after migration is; expectations about the future and whether there is any intention of return. As this is a qualitative research, the results correspond to the analysis of the collected reports and, therefore, it was concluded that besides the economic factor, the interviewees revealed violence as a repulsion factor in Brazil. It was noticed in the speeches a feeling of disenchantment in relation to Brazil, having no intention, on the part of the interviewees, to return to the country of origin.